Optimizacija proizvodnje električne energije z uporabo modificiranega algoritma diferenčne evolucije - Glotić, Arnel (visokošolska dela, 2015)
The dissertation addressed the optimization of electrical energy production from hydro power plants and thermal power plants. It refers to short-term optimization and presents a complex optimization problem. The complexity of the problem arises from an extensive number of co-dependent variables and power plant constraints. According to the complexity of the problem, the differential evolution algorithm known as the successful and robust optimization algorithm was selected as an appropriate algorithm for optimization. The performance of this differential evolution algorithm is closely connected with a control parameters' set and its capabilities being inter alia improved by the algorithm's parallelization. The capabilities of achieving a global optimal solution within the optimization of electrical energy production are improved by the proposed modified differential evolution algorithm with new parallelization mode. This algorithm's performance is also improved by its proposed dynamic population size throughout the optimization process. In addition to achieving better optimization results in comparison with the classic differential evolution algorithm, the proposed dynamic population size reduces convergence time. The improvements of this algorithm presented in the dissertation, besides power plant models mostly used in scientific publications, were also tested on the power plant models represented by real parameters'. The optimization of electrical energy from hydro and thermal power plants is followed by certain criteria; satisfying system demand, minimizing usage of water quantity per produced electrical energy unit, minimizing or eliminating water spillage, satisfying the final reservoir states of hydro power plants and minimizing fuel costs and emissions of thermal power plants.
Keywords: diferenčna evolucija; differential evolution; Disertacije; Električna energija; hidroelektrarne; hydro power plants; Optimizacija; optimization; paralelni algoritmi; parallel algorithm; Proizvodnja; sistemske zahteve; system demand; termoelektrarne; thermal power plants